Web based multi criteria decision making using AHP method - Al-Azab, F. G. M.; Ayu, Media Anugerah (2010)
This paper discusses about a useful mechanism that has been built to guide the decision makers in how to make decision for certain problem using AHP method. AHP is one of multi-criteria decision making tools that have been used in decision making. This system will provide an accurate and acceptable result based on several criteria and lternatives provided by the user. The Web Based Multi-Criteria Decision Making System Using AHP Method will provide a convenient, reliable and faster way for the user to make a decision and get the final result of the decision by showing the best alternative based on the most important criteria. It is developed using PHP, MySQL, Apache Server, Dreamweaver, Adobe P hotoshop and JavaScript. This paper presents the development of the WBMCDM system using AHP method.